2017
DOI: 10.1016/j.envres.2017.08.011
|View full text |Cite
|
Sign up to set email alerts
|

Nature-based agricultural solutions: Scaling perennial grains across Africa

Abstract: Modern plant breeding tends to focus on maximizing yield, with one of the most ubiquitous implementations being shorter-duration crop varieties. It is indisputable that these breeding efforts have resulted in greater yields in ideal circumstances; however, many farmed locations across Africa suffer from one or more conditions that limit the efficacy of modern short-duration hybrids. In view of global change and increased necessity for intensification, perennial grains and long-duration varieties offer a nature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 43 publications
1
25
0
1
Order By: Relevance
“…Moreover, many farmers are women who have less direct access to land, resources, and information updates than men, which often leads to misinformed management decisions. Some studies found that women-headed households had lower yields than those headed by men (a pattern also found in Onoja Chapter 4), likely associated with poorer households needing to work extra for wealthier farmers for cash, usually right when they need to work the most on their own farms (Peter et al 2017).…”
Section: Scalementioning
confidence: 77%
See 2 more Smart Citations
“…Moreover, many farmers are women who have less direct access to land, resources, and information updates than men, which often leads to misinformed management decisions. Some studies found that women-headed households had lower yields than those headed by men (a pattern also found in Onoja Chapter 4), likely associated with poorer households needing to work extra for wealthier farmers for cash, usually right when they need to work the most on their own farms (Peter et al 2017).…”
Section: Scalementioning
confidence: 77%
“…According to one study, maize production under the current situation is optimal on 28 per cent of African agricultural land, suitable on 59 per cent, and unsuitable on 13 per cent (Peter et al 2017). The same study concluded that intercropping to utilize biological nitrogen fixation can benefit areas that are suboptimal for maize.…”
Section: Soil Nutrient Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…Perennial grains have considerable potential to help address this problem; their positive impacts on soils have been widely documented, yet they are not necessarily associated with high costs or labor requirements, as shown in the case or rice (Huang et al 2018). Peter et al (2017) emphasize the potential of perennial grains (specifically sorghum and pigeon pea) to contribute to sustainable agricultural intensification in Africa, especially where topography and/or farming practices have resulted in erosion or depletion of soil organic matter. Where the productive capacity of land is low, qualities like soil improvement, stabilization, and water-stress tolerance may well compensate for lower maximum theoretical yields and boost production potential over time.…”
Section: What Characterizes Smallholder Farming Systems and What Arementioning
confidence: 99%
“…Furthermore, these crops are also dryland crops, suitable for semi‐arid areas with water scarcity, and it should be highlighted that pigeonpea can add 70–100 kg of nitrogen per hectare annually to the soil . These are thus climate smart crops that are instrumental for adapting to climate change in dry zones.…”
Section: Introductionmentioning
confidence: 99%